2017
DOI: 10.1038/labinvest.2017.62
|View full text |Cite
|
Sign up to set email alerts
|

Adrenocorticotropic hormone and 1,25-dihydroxyvitamin D3 enhance human osteogenesis in vitro by synergistically accelerating the expression of bone-specific genes

Abstract: To improve definition of the physical and hormonal support of bone formation, we studied differentiation of human osteoblasts in vitro at varying combinations of ACTH, 1α,25-dihydroxyvitamin D3 (1,25(OH)2D), and extracellular calcium, with and without added cortisol. Bone mineralization, alkaline phosphatase activity, and osteoblast-specific markers RunX2, osterix, and collagen I increased with 10 pM ACTH, 10 nM 1,25(OH)2D, or at 2mM calcium with important synergistic activity of combinations of any of these s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 41 publications
(55 reference statements)
0
25
0
1
Order By: Relevance
“…However, there are considerable disagreements of the direct effect of 1,25OHD in osteogenic differentiation and mineralization ( St-Arnaud, 2008 ; Tarroni et al, 2012 ; van Driel and van Leeuwen, 2014 ). In human osteoblasts, 1,25OHD mostly showed stimulatory effects on osteogenic differentiation and mineralization ( Prince et al, 2001 ; Chen et al, 2002 ; Jorgensen et al, 2004 ; Zhou et al, 2006 ; Tourkova et al, 2017 ; Li et al, 2018 ), but with a few exceptions ( Viereck et al, 2002 ); In rat osteoblasts, the responses to 1,25OHD showed either inhibitory effects or no effects ( Harrison et al, 1989 ; Kim and Chen, 1989 ); In mouse osteoblasts, the differentiation and mineralization of osteoblasts showed the most inconstant responses to 1,25OHD with either no effects, inhibition, or facilitation ( van Driel and van Leeuwen, 2014 ; Chen et al, 2016 ; Kim et al, 2016 ; Xiong et al, 2017 ); Limited studies have been done in chicken osteoblasts, but the available data suggested, in general, that 1,25OHD showed an inhibitory effect on osteoblast differentiation and mineralization ( Broess et al, 1995 ; Pande et al, 2015 ). These inconsistent results may be due to various experimental factors, such as species, cell stage, cell origin, treatment time, and dosage, and the presence of extracellular factors in each study ( Czekanska et al, 2012 ; van Driel and van Leeuwen, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, there are considerable disagreements of the direct effect of 1,25OHD in osteogenic differentiation and mineralization ( St-Arnaud, 2008 ; Tarroni et al, 2012 ; van Driel and van Leeuwen, 2014 ). In human osteoblasts, 1,25OHD mostly showed stimulatory effects on osteogenic differentiation and mineralization ( Prince et al, 2001 ; Chen et al, 2002 ; Jorgensen et al, 2004 ; Zhou et al, 2006 ; Tourkova et al, 2017 ; Li et al, 2018 ), but with a few exceptions ( Viereck et al, 2002 ); In rat osteoblasts, the responses to 1,25OHD showed either inhibitory effects or no effects ( Harrison et al, 1989 ; Kim and Chen, 1989 ); In mouse osteoblasts, the differentiation and mineralization of osteoblasts showed the most inconstant responses to 1,25OHD with either no effects, inhibition, or facilitation ( van Driel and van Leeuwen, 2014 ; Chen et al, 2016 ; Kim et al, 2016 ; Xiong et al, 2017 ); Limited studies have been done in chicken osteoblasts, but the available data suggested, in general, that 1,25OHD showed an inhibitory effect on osteoblast differentiation and mineralization ( Broess et al, 1995 ; Pande et al, 2015 ). These inconsistent results may be due to various experimental factors, such as species, cell stage, cell origin, treatment time, and dosage, and the presence of extracellular factors in each study ( Czekanska et al, 2012 ; van Driel and van Leeuwen, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…After mineralization in bone matrix, deposition of calcium around bone tissue can be detected by calcium staining experiments, including Alizarin Red S 7 . The mineralization of bone matrix is mainly promoted by induction of collagen type I alpha 1 chain (COL1A1), 8 osteocalcin (OC), 9 osteopontin (OPN), 10 bone sialoprotein (BSP), 11 transforming growth factors‐β (TGF‐β), 12 and bone morphogenic proteins (BMPs) 13 . Moreover, Runt‐related transcription factor 2 (RUNX2), 14 osterix (OSX), 15 distal‐less homeobox 5 (DLX5), 16 and β‐catenin 17 are known to play a pivotal role in osteoblast differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…A study assessed whether incubation with the ACTH may influence human osteoblasts differentiation. At the dose of 10 pM, ACTH exposure resulted in the enhancement of osteogenesis by accelerating the expression of bone-specific genes (e.g., collagen I, biglycan, the vitamin D receptor, and TGF-β) [22]. Such findings have also been confirmed elsewhere [23].…”
Section: Pre-clinical Evidencementioning
confidence: 59%